Forming Students' Character with The Story Learning Model (Qishah Qurani) - Fadhilah, Nurul; Jakaria, Jakaria; Mubarok, Muhammad Ramdan (Jurnal Pendidikan Karakter JAWARA (Jujur, Adil, Wibawa, Amanah, Religius, Akuntabel), 2023)
Fundamental character building is a benchmark for students in developing their potential. Of course, this is one of the most potentials that should be able to find one's identity. The Qur'an finds formulas in overcoming and forming characters according to its capacity, one of which is by the method of story. The story (qishah) in the Qur'an is unique and/or idiosyncratic in two main respects. First, paying attention to the aspect of truth and factuality (waq'iyah) is not just imagination. Second, pay attention to the goals and objectives of the exposure of the story. The purpose of the stories in the Qur'an (qishah qurani) is participation with other models or styles that the Qur'an utilizes to realize religious and educational goals and objectives, of which the Qur'anic story is among the most important methods. In Islamic education, many methods can be used to improve and develop, educate, care for, and strengthen every potential given by Allah to students, one of which is the story-learning model. This model is one of the models or solutions for teachers as students in teaching story material in the classroom and outside the classroom.